منهج الكتابة التاريخية عند ابن خلدون - زين, عبد الله (جامعة الوادي - University of Eloued, 2019)
Ibn Khaldoun is considered as one of the intellectuals who took part in history, Arabic Islamic civilization as well as the human one. Because of his deep look of history, he linked history with social life so that to make laws to differ fake historic facts from true ones. In addition, he took part in history events, and established the historic writing based on scientific rules like the critical spirit, relativity belief. Moreover, he depended on the induction and comparison in the historic writing. Above all, it's clear that Ibn khaldoun's way of historic writing is too important because he added scientific spirit to history so that to protect history from myths and legends.
مقال
Keywords: ابن خلدون,منهج الكتابة التاريخية,التاريخ,علم العمران البشري